2016
DOI: 10.1289/ehp.1408171
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Lead Exposure and Associations with Selected Cancers: The Shanghai Men’s and Women’s Health Study Cohorts

Abstract: BackgroundEpidemiologic studies of occupational lead exposure have suggested increased risks of cancers of the stomach, lung, kidney, brain, and meninges; however, the totality of the evidence is inconsistent.ObjectiveWe investigated the relationship between occupational lead exposure and cancer incidence at the five abovementioned sites in two prospective cohorts in Shanghai, China.MethodsAnnual job/industry-specific estimates of lead fume and lead dust exposure, derived from a statistical model combining exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 31 publications
0
43
0
2
Order By: Relevance
“…Hence, there is little information about specific cancer sites among men with high exposure in this cohort. Liao et al 30 studied cancer incidence among approximately 7000 lead-exposed men and women workers in two plants in Shanghai, comparing them with a large number of unexposed workers, and using a job-exposure matrix to classify workers into none, low, medium and high exposure to either lead dust or fumes. Overall, there were suggestions of an excess among exposed versus non-exposed workers for brain cancer (rate ratio (RR) 1.8, 0.704.28, 10 exposed cases) and kidney cancer (RR 1.4, (0.9–2.3), 17 exposed cases).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is little information about specific cancer sites among men with high exposure in this cohort. Liao et al 30 studied cancer incidence among approximately 7000 lead-exposed men and women workers in two plants in Shanghai, comparing them with a large number of unexposed workers, and using a job-exposure matrix to classify workers into none, low, medium and high exposure to either lead dust or fumes. Overall, there were suggestions of an excess among exposed versus non-exposed workers for brain cancer (rate ratio (RR) 1.8, 0.704.28, 10 exposed cases) and kidney cancer (RR 1.4, (0.9–2.3), 17 exposed cases).…”
Section: Discussionmentioning
confidence: 99%
“…Lead is a highly prevalent and persistent environmental toxicant that is widely used in different industries . Because of its chemical properties, lead is used in a wide variety of industries and is the fifth most frequently used metal worldwide .…”
Section: Introductionmentioning
confidence: 99%
“…Lead's effect on the haematologic system is typically manifested by a mild hypochromic, microcytic, sometimes haemolytic, anaemia . Some studies have suggested carcinogenic effects of lead for stomach, lung, kidney, brain and meninges, though the evidence in this area has conflicting results . Overall, high BLLs have been associated with increased mortality from various causes …”
Section: Introductionmentioning
confidence: 99%
“…Since smoking is a predictor of blood lead,25 the potential for residual confounding by other carcinogens in cigarette smoke cannot be ruled out as an explanation for these findings. Exposure to lead, as estimated by a job-exposure matrix, was associated with a non-significant increase in kidney cancer risk among participants in the Shanghai Men’s and Women’s Health Study cohorts 4. Kidney cancer has been assessed in two occupational cohort studies of lead-exposed workers that did not adjust for smoking.…”
Section: Discussionmentioning
confidence: 99%